The Influence of Motivation, Self-Control and Financial Literacy on Financial Management of Gen Z Students in Tangerang - Ika Pratiwi Simbolon; Christy Ayu Sarah Panjaitan; Lilis Susilawaty; Viola Anginette Muljo (Indonesian Journal of Business Analytics, 2025)
This study aims to examine the effect of motivation, self-control, and financial literacy on the financial management of Generation Z students in Tangerang. Using a purposive sampling method, 101 students who met the criteria of being part of Generation Z and domiciled in Tangerang were selected as respondents. The research employed a quantitative descriptive approach with data analyzed using SPSS. The findings reveal that motivation and financial literacy significantly influence financial management among Generation Z students, while self-control does not show a significant effect. These results underscore the importance of strengthening financial literacy and motivational factors to foster better financial behavior among young individuals. In today's rapidly changing economic environment, financial literacy provides a foundation for individuals to make informed financial decisions, manage their income wisely, and avoid risky financial behavior. Moreover, motivation plays a critical role in shaping an individual's willingness to plan, control, and pursue financial goals. Even though self-control is often associated with prudent financial behavior, this study finds it insufficient as a sole predictor of sound financial management among Generation Z. These insights are expected to serve as a valuable reference for educators, policymakers, and financial institutions in designing targeted programs that empower Generation Z with the knowledge and drive needed to make responsible financial decisions and achieve financial well-being in the future.